A construção do plano de formação a partir das necessidades formativas dos professores - Paula, Jaqueline dos Santos (2021)
Teachers training needs to produce effective changes in the educational context in which they are inserted. Owing to the specificities and uniqueness of these contexts it is crucial to comprehend that teachers training processes fail to offer formulas capable of solving the challenges faced daily in their classrooms. Nevertheless, if training should result in improving education for students it is not possible to think generally about it. Thus, a question mobilized this research: How can teachers' training needs guide the collective construction of a training plan?". This question led to the following general goal: analyze the training needs of teachers to collectively develop a training plan. In order to achieve this goal, the qualitative approach was applied. The research was carried out in a private school in the central region of São Paulo with teachers from the early years of elementary school and the data were obtained through reflective meetings- this procedure aims to provide reflective actions about the teaching practice based mainly on moments of listening, self-assessment and exchange of experiences. For data generation, the meetings were transcribed and the prose examination was the way chosen to analyse them. The following theoretical framework was adopted: André and Lüdke (2018), Canário (1998), Marcelo García (1999), Imbérnon (2006, 2010), Rodrigues (s.d.) among others. The results indicate that teachers value the space for exchange, sharing of practices and need these spaces to be increasingly expanded since they believe that continuing education can contribute to their professional development. Besides that, teachers also have training needs regarding to inclusive education, understanding of the school curriculum and meaningful learning. In addition, through these meetings the research allowed a reflective and collective experience in the construction of a training plan in which teachers participated in a collaborative and authorial way